Which Securities Regulation Promotes Crowdinvesting? - Lars Hornuf; Armin Schwienbacher (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2014)
In this paper, we show that too strong investor protection may harm small firms and, thus, entrepreneurial initiatives. This situation is particularly relevant in crowdinvesting, which refers to a recent financial innovation originating on the Internet. In general, securities regulation offers exemptions to prospectus and registration requirements. From an analysis of selected countries, we offer first evidence that portals shape the securities contracts they provide to startups based on these exemptions. This, in turn, can limit the amount of capital raised by the firms as well as the type of investors participating in the campaigns. Finally, we offer a `law and finance' analysis of recent reforms of securities regulation in different countries that have been initiated as a means to encourage crowdinvesting.
urn:nbn:de:bvb:19-epub-20975-9
Keywords: G20; G18; G38; K22; 330; crowdinvesting; crowdfunding; securities regulation; investor protection